Case 3722: Scarabaeus gazella Fabricius, 1787 (currently Digitonthophagus gazella or Onthophagus gazella; Insecta, Coleoptera, Scarabaeidae): proposed conservation of usage of the specific name by designation of a neotype - Génier, François; Krell, Frank-Thorsten (Bulletin of Zoological Nomenclature, 2017)
The purpose of this application, under Article 75.6 of the Code, is to conserve the specific name Digitonthophagus gazella (Fabricius, 1787) for a common African species of dung beetle (also known as Onthophagus gazella) that was successfully introduced into multiple areas all over the world. The species is of high economic importance as it is used as a biological control agent of pest flies and provides ecological services through the rapid burial of cattle dung. Scarabaeus gazella Fabricius, 1787 is a junior synonym of Scarabaeus catta Fabricius, 1787, now known as Digitonthophagus catta. If the principle of priority is applied, the name of the widely distributed species, would be Scarabaeus dorcas Olivier, 1789, a name that has been considered a junior synonym of Scarabaeus gazella/Scarabaeus catta since 1833. We propose to conserve the name Digitonthophagus gazella (Fabricius, 1787) for the widely introduced species through the designation of a neotype from voucher material of the original introduction into Hawaii. All feedback received from colleagues was supportive for the proposed designation of a neotype in order to maintain prevailing usage of the name D. gazella.
Keywords: Afrotropical; biological control of dung; Digitonthophagus; dung beetle; Nomenclature; Onthophagus; Onthophagus gazella; pasture improvement; Recent; Scarabaeidae; Scarabaeinae; taxonomy